650 The Association between Sleep and Psychological Distress among New York Healthcare Workers During the COVID-19 Pandemic - Diaz, Franchesca; Bramley, Sean; Venner, Hadiah; Shaw, Kaitlin; McMurry, Cara; Cornelius, Talea; Schwartz, Joseph; Shechter, Ari; Abdalla, Marwah (Sleep (New York, N.Y.), 2021)
Introduction Healthcare workers (HCWs) treating patients with COVID-19 report high rates of acute stress, depressive and anxiety symptoms. We examined whether sleep disturbances were associated with psychological distress in New York City (NYC) HCWs during the initial peak of COVID-19 in-patient admissions (April 9 - May 11, 2020). Methods HCWs (physicians, nurses, and advanced practice providers) completed a web-based survey which screened for acute stress (4-item Primary Care PTSD screen), depressive symptoms (Patient Health Questionnaire-2), and anxiety (2-item Generalized Anxiety Disorder scale). Past week insomnia symptoms were assessed with a modified item from the Insomnia Severity Index (5-point Likert Scale: none, mild, moderate, severe, very severe). Insomnia was defined as having “moderate, severe, or very severe” symptoms. Short sleep (SS) was defined as self-reported sleep duration <6 hours per day. Poisson regression analyses predicting psychological distress from SS and, separately insomnia. adjusting for age, gender, race/ethnicity, clinical setting (COVID-focused or not COVID-focused), physician vs. non-physician status, and redeployment status, were performed. Results Data included 813 HCWs (80.6% female, 59.0% White, 75.6% worked in a COVID-focused setting). Mean sleep duration was 5.79 ± 1.22 hours/night. The prevalence of SS and insomnia were 38.8% and 72.8%; the prevalence of acute stress, depressive symptoms, and anxiety were 57.9%, 33.8% and 48.2%, respectively. Having SS, vs. not was associated with acute stress (adjusted prevalence ratio [PR]: 1.21, 95% CI: 1.07, 1.31), depressive symptoms (PR: 1.65, 95% CI: 1.35, 2.02), and anxiety (PR: 1.51, 95% CI: 1.30, 1.74). Presence of insomnia symptoms vs. “none or mild” was associated with acute stress (PR: 1.92, 95% CI: 1.57, 2.34), depressive symptoms (PR: 3.13, 95% CI: 2.16, 4.52), and anxiety (PR: 2.40, 95% CI: 1.86, 3.11). Conclusion Among NYC HCWs, sleep disturbances, including SS and insomnia symptoms during COVID-19 are common. In our study, SS and insomnia were associated with acute stress, depressive symptoms, and anxiety in HCWs, however further research on whether a bidirectional relationship exists between sleep and psychological distress during the COVID19 pandemic are still needed. Support (if any):